Muslim Investors' Behavior in Deciding to Invest in Sharia Shares in the Period 2018-2023: A Systematic Literature Review - Taufik, Ghofar; Rusmana, Oman (Penerbit Goodwood, 2023)
Purpose: The author's goal in this study is to investigate the factors that influence Muslim investors' decisions to invest in Sharia-compliant shares. This study aims to provide a detailed description of insider investor decision-making behavior. Methodology: Using the Scopus database and Google Scholar, the author analyzed 10 articles published between 2018 and 2023 to map the pattern of behavior of Muslim investors in deciding whether to invest in Sharia shares. Data was collected and reviewed before doing an analysis review, followed by a systematic literature review to support the next study. Results: Findings and results highlight that the behavior of Muslim investors is influenced by several factors, like investor ethics, motivation, patterns of investment, and religious factors. While the factors that influence the decision to invest in Islamic stocks are the level of return and investment risk. The implications of this research are to provide an understanding of the factors that influence Muslim investors' decisions in choosing Islamic equity investments, to provide insight into past investment experiences that influence Muslim investors' decisions, to improve perceptions of the risk of investing in Islamic equities so that investors can reduce risk and achieve better results from their investments. In addition, Islamic financial institutions can provide good services to Muslim investors and the government can take more appropriate steps to develop the Islamic financial market.